The factors that influence students’ participation in soft skills activities: a case study of final year students in Faculty of Administrative Science and Policy Studies at UiTM Melaka City Campus / Syahin Syahmi Mohd Sapuan and Syahrul Effendi Ahmad - Mohd Sapuan, Syahin Syahmi; Ahmad, Syahrul Effendi (Faculty of Administrative Science and Policy Studies, 2013)
This research intends to focus on the factors that influence student participation in soft skills activities which is the key factor that to attract to students to participate in soft skills activities. This research hopes to provide useful insight into how to attract the students to join the soft skills by providing the several factors to be considered as the alternative way in order to have more participation from students. Therefore, the most influence factors in this studies need to be concentrates by the institutes especially the party who in-charge this kind of activities. The objectives of this study are to identify the relationship between the factors (peers, interests, and compulsory) and the students involvement in the activities of soft skills in an institute of higher learning. The method to conduct this study was through the survey which was distribute in the form of questionnaire to 171 out of 231population of final year students who had become the target group for this study. Several tests were conducted to meet the objectives of the study such as descriptive analysis, normality analysis, reliability analysis, Pearson’s product-moment correlation, and finally the multiple regressions to determine which of the three factors that highly gives most influence factor towards students. All the information and data were collected through the primary and secondary data such as books, journals, internet, and etc. Hopefully, this research will contribute something to the educational setting especially UiTM organization.